Um estudo sobre o Serviço de Convivência e Fortalecimento de Vínculos destinados à população idosa - Lopes, Laís Brunozi Avelar (2025)
The present study aims to analyze how the Service of Coexistence and Strengthening of Bonds for Older Persons (SCFV) and the intersectoral dimensions that characterize it are incorporated into the National Policies that precede its typification. It is a documentary analysis, carried out through the review of three public policies, National Policy for the Elderly, National Health Policy for the Elderly and National Policy for Social Assistance and, complementarily, a description of the National Typification of Social Assistance Services. A systematic search procedure for keywords and a content analysis matrix based on Minayao were developed, where thematic categorization, coding and synthesis were carried out. The results showed that the SCFV was not appointed before 2009, but the implicit presence of elements that already announced its need in both policies. It showed that Brazilian policies recognize intersectoriality, but lack operational mechanisms that fully implement it, leaving critical gaps in execution. The need for funding in training and operational instruments is pointed out.